Secundiparas following a failed vacuum delivery-factors associated with a successful vaginal delivery: a historical prospective cohort - Orna Reichman; Zvi Ehrlich; Ramy Suday; Hen Sela; Gila Gold; Arnon Samueloff; Sorina Grisaru-Granovsky (BMC, 2022)
Abstract Background Few studies have focused on the delivery subsequent to a failed vacuum delivery (failed-VD) in secundiparas. The objective of the current study was to examine the factors associated with a vaginal delivery following a failed-VD. Methods An historical prospective cohort. Obstetric characteristics of secundiparas who underwent a planned caesarean delivery (CD) were compared to those who elected a trial of labour (TOLAC) at single medical-centre, throughout 2006-2019. The latter were further analysed to study for factures associated with successful vaginal birth (VBAC). Results Among the 115 secundiparas included, 89 (77%) underwent TOLAC. Compared to women who underwent an elective CD, those who underwent TOLAC were younger by a mean of 4 years, were more likely to have conceived spontaneously, and had a more advanced gestation by a mean of 10 days. VBAC was achieved in 62 women (70%). New-borns of women with VBAC had in average a lower birth weight compared to those with failed TOLAC, (-)195 g ± 396 g versus ( +)197 g ± 454 g respectively, P < 0.01. Having a higher neonatal birthweight at P2 by increments of 500 g, 400 g or 300 g was associated with a failed TOLAC; OR of 9.7 (95%CI; 2.3, 40.0), 11.5 (95%CI; 2.8, 46.7) and 4.5 (95%CI; 1.4, 13.9), respectively. Conclusions Among secundiparas with a previous CD due to a failed-VD, the absolute difference of neonatal BW was found to be significantly associated with achieving VBAC.